THE EFFECT OF CHEWING APPLES AND PEARS AFTER EATING CHOCOLATE BISCUIT ON TOOTH PLAQUE : PENGARUH MENGUNYAH BUAH APEL DAN BUAH PIR SETELAH MAKAN BISKUIT COKELAT TERHADAP PLAK GIGI - Monica Elisa Megawati; Ignatius Sulistyo Jatmiko; Aloysia Supartinah (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Plaque is one of causes of dental caries among children because of habit of eating snacks that are cariogenic such as chocolate flavored biscuits. Some of fruits contain water and fiber such as apple and pear can mechanically reduce accumulation of dental plaque. This study aims to determine the effect of chewing apple and pear after eating chocolate flavored biscuits toward dental plaque among children aged 8 to 10. Material and Methods: This research is a quasi-experimental with pretest – post test control group design, was conducted in SD NegeriJogkang, Ngaglik, Sleman, Yogyakarta and 24 children aged 8 to 10 were involved in this study. The children were divided into three groups and each group consists of 8 children. First group was treated by chewing 50 grams of apple after eating chocolate flavored biscuits, second group was treated by chewing 50 grams of pear after eating chocolate flavored biscuits and third group was treated by eating chocolate flavored biscuits without chewing any fruits, then crossover. Dental plaque score was measured using PHP-M index from Martens and Meskin which was done before and after treatment. Data of dental plaque score then analyzed using One Way ANOVA and Post-Hoc LSD (Least Significant Difference) (p0,05). Results and Discussions: The results showed differences of mean and standard deviation score of dental plaque before and after chewing apple by 17,45±1,95; chewing pear by 11,58±1,90; consuming biscuits without chewing fruits by 2,91±1,24. The result of one-way ANOVA analysis showed there were significant differences in all groups (p<0,05). The result of Post-Hoc LSD tests showed dental plaque score differences between groups which chewing apple and pear (p<0,05). Conlusion: Based on conducted study, the conclusion can be drawn is chewing apple after eating chocolate flavored biscuits is further reduced dental plaque score than chewing pear in children age 8 to 10.